Generalized Rough Γ-Hyperideals in Γ-Semihypergroups. (7th July 2014) - Yaqoob, Naveed; Haq, Shamsul
Abstract : Davvaz (2008) introduced the concept of set-valued homomorphism and T -rough sets in a group. In this paper, we consider the set-valued homomorphism T on Γ -semihypergroup H to interpret the lower and upper approximations. We study the roughness of ( m, n ) bi-Γ -hyperideals and ( m, n ) quasi-Γ -hyperideals in terms of set-valued homomorphisms, which are extended notions of ( m, n ) bi-Γ -hyperideals and ( m, n ) quasi-Γ -hyperideals of Γ -semihypergroups.